Co-Occurrence of Myeloid Sarcoma of the Lymph Node and Acute Monocytic Myeloid Leukemia: A Case Report and Literature Review - Misbahuddin Khaja; Toolsie Omesh; Masooma Niazi; Danial Shaikh; Sitarama Arvind Mudunuru; Olga Alexandra Reyes; Sandeep Malik (Case Reports in Oncology, 2018)
Background: Acute myeloid leukemia (AML) is the most common leukemia in adults. According to the French-American-British (FAB) system, monocytic leukemia is classified as M5. Myeloid sarcoma further occurs in 3–5% of AML. This is defined as an extramedullary tumor of myeloid cells in the lymph nodes, soft tissues, periosteum, bone, central nervous system (CNS), spinal cord, intestine, mediastinum, prostate, uterus, or ovaries. Case Presentation: Here, we describe the case of a 29-year-old female who presented with fever, swelling of gums, neck pain, and weakness, which had persisted for 1 week. The patient had a white blood cell (WBC) count of 53.5 K/μL, and a peripheral smear revealed a myeloid blast cell (blast) percentage of 8%. Computed tomography (CT) of the neck indicated lymphadenopathy. Fine needle aspiration of the cervical lymph node showed groups of atypical immature myeloid cells, mixed with occasional megakaryocytes, and infiltration of eosinophilic myeloid cells into the lymph node, consistent with myeloid sarcoma. Flow cytometry analysis revealed intermediate to large circulating blasts, with irregular nuclei, fine chromatin, and distinct nucleoli, indicative of AML, with monocytic differentiation. The patient responded well to chemotherapy with fludarabine, cytarabine, granulocyte colony stimulating factor (G-CSF), and idarubicin; WBC counts returned to normal and patient was discharged to home. Conclusion: Myeloid sarcoma of the lymph node is a rare co-occurrence with AML. Results of our study are consistent with the conclusion that early diagnosis and appropriate treatment improve survival.